Investigations on metabolic diseases of horses in Egypt - Aboelmaaty, Amal M.; Ahdy, Ahmed M.; El-khodery, Sabry; Elgioushy, Magdy (Frontiers in Veterinary Science, 2025)
IntroductionObesity is a significant risk factor that predisposes horses to laminitis, equine metabolic syndrome, arthritis, heart disease, and respiratory issues.MethodsMares showing overweight or laminitis (N = 30), different BCS (N = 90) weighing 350–550 Kg were subjected to clinical and rump fat assessments. Blood samples were collected to measure circulating estradiol, progesterone, cortisol, insulin, insulin-like growth factor-1 (IGF-1), and leptin. Additionally, glucose, cholesterol, triglycerides, total proteins, albumin, nitric oxide (NO), lactate dehydrogenase (LDH), glutathione reduced, catalase, and serum amyloid A were measured. Statistical comparisons among mares were based on laminitis, hyperinsulinemia, overweight, the combination of hyperinsulinemia and overweight, and rump fat levels.ResultsLaminitis was associated with lower glucose levels (4.83 ± 0.16 vs. 5.56 ± 0.52 mmol/L; p = 0.002) and body weight (380.0 ± 10.95 vs. 447.6 ± 65.98 kg; p = 0.02), as well as higher albumin (3.78 ± 0.01 vs. 3.11 ± 0.62 g/dL; p = 0.015), catalase (193.64 ± 69.29 vs. 37.45 ± 7.57 U/mL; p = 0.001), IGF-1 (29.35 ± 17.31 vs. 20.29 ± 6.48 ng/mL; p = 0.043), and the glucose/insulin ratio (0.77 ± 0.68 vs. 0.44 ± 0.030; p > 0.05). Obesity (>450 Kg) was associated with increased glucose levels (5.60 ± 0.54 vs. 5.15 ± 0.39 nmol/L; p = 0.018) and reduced IGF-1 (16.44 ± 4.51 vs. 28.24 ± 3.90 ng/mL; p < 0.001), albumin (2.98 ± 0.67 vs. 3.46 ± 0.53 g/dL; p = 0.041), albumin/globulin ratio (0.72 ± 0.07 vs. 0.98 ± 0.11; p = 0.048), and glucose/insulin ratio (0.34 ± 0.14 vs. 0.71 ± 0.58; p = 0.009). Hyperinsulinemia (>20 μU/L) was associated with significant reduction in albumin (2.67 ± 0.59 vs. 3.56 ± 0.37 g/dL; p = 0.0001), albumin/globulin ratio (0.57 ± 0.24 vs. 1.01 ± 0.32 g/dL; p = 0.0001), catalase (17.23 ± 2.24 vs. 100.67 ± 30.99 U/mL; p = 0.021), NO (19.23 ± 2.24 vs. 21.35 ± 1.29 mmoL/mL; p = 0.002), glucose (5.44 ± 0.53 vs. 5.61 ± 0.38 mmol/L; p = 0.038), and glucose/insulin ratio (0.18 ± 0.04 vs. 0.72 ± 0.41; p = 0.0001). In contrast, globulin levels were significantly elevated (5.02 ± 1.02 vs. 3.85 ± 1.10 g/dL; p = 0.0001). The combination of hyperinsulinemia and obesity was associated with significant decreases in (p = 0.0001) albumin, albumin/globulin, and IGF-1, and increases in LDH, NO, globulins (p = 0.006). Additionally, NO levels were significantly reduced in hyperinsulinemia mares with lower body weight (p = 0.0001).ConclusionObesity, whether assessed by rump fat or overweight, is not always associated with hyperinsulinemia or with metabolic or endocrinologic abnormalities in mares. Conversely, hyperinsulinemia is not always associated with obesity but is related to insulin resistance and dysregulation.